Deskripsi Kesadaran Metakognitif Siswa SMP Negeri 14 Pontianak pada Mata Pelajaran IPA - Riyadi, M. Akbar Slamet; Ningsih, Kurnia; Tenriawaru, Andi Besse; Afandi, Afandi (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This research aims to describe the metacognitive awareness of aspects of knowledge about cognition and aspects of cognitive regulation of students at SMP Negeri 14 Pontianak in science subjects. The method used in this research is quantitative descriptive. The population in this study was class VIII students at SMP Negeri 14 Pontianak, totaling 308 students, divided into 9 classes, namely VIII A, VIII B, VIII C, VIII D, VIII E, VIII F, VIII G, VIII H, and VIII I. The sampling technique uses the Slovin formula with a sample size of 75 students. The instrument for this research is the Metacognitive Awareness Inventory for Science (MAIS) instrument, developed by modifying the Metacognitive Awareness Inventory (MAI) instrument developed by Schraw & Deninson (1994). The results of the research obtained: 1) description of metacognitive awareness aspects of knowledge about cognition of students at SMP Negeri 14 Pontianak, 10.67% of students in the developing category, 77.33% of students in the good category (ok), and 12% of students in the very good (super); and 2) description of metacognitive awareness of aspects of cognitive regulation of students at SMP Negeri 14 Pontianak, 6.67% of students in the developing category, 89.33% of students in the good category (ok), and 4% of students in the very good (super) category.